2021
DOI: 10.11594/jesi.01.01.03
|View full text |Cite
|
Sign up to set email alerts
|

UMKM, Kesetaraan Gender dan Pemberdayaan Perempuan di Indonesia

Abstract: Mempromosikan kesetaraan gender telah menjadi kenyataan yang diakui secara global dan dapat diterima. Masalah gender juga telah diidentifikasi sebagai hal yang penting untuk pencapaian tujuan pembangunan nasional. Bahkan, pencapaian kesetaraan gender tidak hanya dilihat sebagai tujuan itu sendiri, tetapi juga sebagai katalisator, dan sine-qua-non bagi pencapaian pembangunan berkelanjutan. Penelitian ini mencoba menilai tingkat pencapaian kesetaraan gender dan pemberdayaan perempuan dengan menggunakan tiga indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
1
7
0
9
Order By: Relevance
“…These results concur with those of Sari et al (2021), who found that strong sales figures can boost SMEs' competitiveness by demonstrating that the goods and services they provide are in high demand. SMEs can enhance their reputation and broaden their market reach through successful sales outcomes.…”
Section: The Influence Of Marketing Performance On the Competitivenes...supporting
confidence: 90%
“…These results concur with those of Sari et al (2021), who found that strong sales figures can boost SMEs' competitiveness by demonstrating that the goods and services they provide are in high demand. SMEs can enhance their reputation and broaden their market reach through successful sales outcomes.…”
Section: The Influence Of Marketing Performance On the Competitivenes...supporting
confidence: 90%
“…It leads to abolish the perception that women overlook in development. There are some indicators that can be used to mention that women are involved in developing such as participating women in education from middle level and high grade, working and involving in political determination (Sari et al, 2021). However, in order to achieve this goal, women still confront some arduous conditions typically in gender.…”
Section: Resultsmentioning
confidence: 99%
“…Pembahasan dapat menekankan bahwa pemberdayaan perempuan dalam UMKM tidak hanya menjadi katalisator untuk pertumbuhan ekonomi lokal tetapi juga kontribusi positif terhadap pencapaian Tujuan Pembangunan Berkelanjutan. Peningkatan kapasitas UMKM yang dipimpin perempuan dapat memberikan dampak positif pada pengentasan kemiskinan, kesetaraan gender, dan keberlanjutan ekonomi (Sari, Irwandi, Rochmansjah, Nurdiansyah, & Aslam, 2021).…”
Section: Hasil Dan Pembahasanunclassified